1, 3‐Dipolar cycloadditions of Stone–Wales defective single‐walled carbon nanotubes: A theoretical study. Issue 26 (6th July 2013) - Yang, Tao; Zhao, Xiang; Nagase, Shigeru
Abstract : The presence of Stone‐Wales defects in single‐walled carbon nanotubes (SWNTs) not only leads to new interesting properties, but also provides opportunities for tailoring physical and chemical properties, and expands their novel potential applications. With a two‐layered ONIOM method, 1, 3‐dipolar cycloadditions (1, 3‐DCs) of a series of 1, 3‐dipoles (azomethine ylide, nitrone, nitrile imine, nitrile ylide, nitrile oxide, and methyl azide) with Stone‐Wales defective SWNTs have been investigated theoretically for the first time. The calculated results demonstrate that the bondc, rather than the previously focused central bonda, exhibits the highest chemical reactivity among the defective sites. More interestingly, bondc is even more reactive thermodynamically and kinetically than the perfect CC bond in SWNTs, suggesting the feasibility of utilizing 1, 3‐DC reactions to separate and purify perfect and defective SWNTs. The reactivity order for nonequivalent bonds in defective sites is different from that of [1+2] cycloaddition, indicating that the reactivity order for nonequivalent bonds depends on the kind of the chemical reactions. Except azomethine ylide, nitrile ylide and nitrile imine are found to be good candidates for 1, 3‐DCs upon Stone‐Wales defective SWNTs. The SW‐A and SW‐B defective SWNTs show different chemical reactivity toward nitrile ylide, making it possible to purify and separate the SW‐A and SW‐B defective SWNTs. The SWNT diameters are found to moderately influence the 1, 3‐DC reactivity of both perfect and Stone‐Wales defective SWNTs, implying that Stone‐Wales defective SWNTs with different diameter would be separated experimentally through 1, 3‐DC chemistry. The above 1, 3‐DC reactivity can be well understood in terms of the distortion/interaction theory, which means that instead of frontier molecular orbitals interaction energy, the distortion energy controls the chemical reactivity. © 2013 Wiley Periodicals, Inc. Abstract : In contrast to previous theoretical results, density functional theory calculations reveal that the Stone–Wales defect in armchair single‐walled carbon nanotubes (SWNTs) displays higher thermodynamic and kinetic reactivity than the perfect bond in 1, 3‐dipolar cycloadditions. Small‐diameter defective SWNTs are found to react more easily than large ones.